General Self-Efficacy and Health Literacy Levels of Students Parents: Investigation in Two Primary Schools in Ankara - Altun, Berhiv; Özkan, Seçil (Turkey Health Literacy Journal, 2020)
Parents’ health literacy level is an important factor in health prevention and promotion as well as for community health. Objectives:This study aimed to examine the relationship between general selfefficacy and health literacy levels. Method: This cross-sectional study was conducted between May and June 2016 in two primary schools located in two districts of Ankara. The sample was selected among parents of students attending 1st- 4th years of primary school. Descriptive questions, Turkey Health Literacy and general self-efficacy scales were included in the survey and 226 parents were evaluated. Pearson Chi-square, Fisher’s Exact, Kolmogorov-Smirnov, Mann-Whitney U, Student’st, Kruskal- Wallis one-way analysis of variance and Spearman correlation tests were used for the analysis. Results: 64.6% of participants had inadequate-limited health literacy and general selfefficacy score was 62.63(±10.34). A positive, powerful and statistically significant relationship was found between general self-efficacy and health literacy(r=0,70,p